Monitoring the reaction kinetics of waterborne 2‐pack polyurethane coatings in the dispersion and during film formation. (27th August 2021) - Zhou, Hang; Liu, Yang; Lu, Yijie; Tran, Kenneth; Glenn, Joshua; Zhang, Margaret; Soleimani, Mohsen; Lucas, Frédéric; Winnik, Mitchell A.
Abstract: We examine the nature of the chemical reactions taking place in a waterborne two‐component polyurethane formulation consisting of an acrylic polyol latex and a hydrophilically modified polyisocyanate (hmPIC) based on the trimer of hexamethylene diisocyanate. The hmPIC was diluted with 30 wt.% of an organic solvent to reduce its viscosity and formed small (~20 nm) droplets when dispersed in water. In mixtures of the polyol and hmPIC, we monitored the rate of NCO group disappearance in the dispersed state by FTIR and showed that it varied with the choice of organic solvent. We developed a method based upon 19 F NMR to distinguish the reaction of the NCO groups with OH groups from the polyol from its reaction with water. FTIR measurements on films formed from these dispersions showed how the disappearance of NCO groups depended on relative humidity. In a more semi‐quantitative way, these measurements indicated the relative extent of urethane versus urea formation in these model coatings. Abstract : Functional group evolution in a waterborne polyurethane dispersion.